2015
DOI: 10.1080/08897077.2014.969470
|View full text |Cite
|
Sign up to set email alerts
|

Increased Energy Drink use as a Predictor of Illicit Prescription Stimulant Use

Abstract: Results indicate that the frequency of energy drink use was a significant predictor of the illicit use of prescription stimulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…For example, energy drink users were more likely to be male, 2,5,8,11 employed, 13 have higher AUDIT scores, 3 and they were more likely to engage in various risk behaviors. [2][3][4][5][6][7][8][9][10][11]13,14 In addition, results from the delay discounting tasks replicated results from studies that found that larger monetary rewards are discounted less steeply than smaller rewards 47 and delay discounting of condom-protected sex is steeper when partners are perceived as more desirable and less likely to have an STI. [29][30][31][32][33] The results of this study should be interpreted within the context of several limitations.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…For example, energy drink users were more likely to be male, 2,5,8,11 employed, 13 have higher AUDIT scores, 3 and they were more likely to engage in various risk behaviors. [2][3][4][5][6][7][8][9][10][11]13,14 In addition, results from the delay discounting tasks replicated results from studies that found that larger monetary rewards are discounted less steeply than smaller rewards 47 and delay discounting of condom-protected sex is steeper when partners are perceived as more desirable and less likely to have an STI. [29][30][31][32][33] The results of this study should be interpreted within the context of several limitations.…”
Section: Discussionsupporting
confidence: 74%
“…Although recent nationwide data on energy drink consumption are scarce, some researchers estimate that over 18% of young adults consume energy drinks at least weekly, 2 and, among college students, this percentage may be as high as 39%. 3 Emerging evidence points to a relationship between energy drink use and various risk behaviors, including alcohol abuse, 2-10 cigarette smoking, 2,6-9,11-13 illicit drug use, 2,6-9,11-13 nonmedical use of prescription drugs, 5,6,8,11,14 fighting, 8 and sexual risk behavior. 8 One of the primary aims of this study was to replicate and extend these findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From two waves of data from the study that is the focus of the present analysis, college students who consumed EDs were twice as likely to initiate nonmedical prescription stimulant use one year later compared with students who did not consume EDs, controlling for risk factors and other caffeine consumption (Arria et al, 2010). Other studies have also observed cross-sectional associations between ED consumption and other drug use (Kelly and Prichard, 2016; Kumar et al, 2015; Miller, 2008a; Miller and Quigley, 2011; Terry-McElrath et al, 2014; Trapp et al, 2014; Woolsey et al, 2014; Woolsey et al, 2015). At least three potential mechanisms exist to explain the association.…”
Section: Introductionmentioning
confidence: 90%
“…Approximately one in three U.S. adolescents and young adults consume EDs and energy shots, with estimates as high as 50% for past-month use among college students (Arria et al, 2014; Miller, 2008b; Terry-McElrath et al, 2014; Velazquez et al, 2012; Woolsey et al, 2015). One study reported that 10% of college students consumed EDs at least weekly during the past year (Arria et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%